2017
DOI: 10.1262/jrd.2016-182
|View full text |Cite
|
Sign up to set email alerts
|

Modification of mitochondrial function, cytoplasmic lipid content and cryosensitivity of bovine embryos by resveratrol

Abstract: Resveratrol is a potent activator of NAD-dependent deacetyltransferase sirtuin-1 (SIRT1) and affects lipid metabolism and ATP generation in somatic cells. In the present study, the effects of supplementing culture medium with resveratrol on lipid metabolism, ATP generation, and cryosensitivity of bovine in vitro produced embryos were investigated. Bovine early cleaved-stage embryos were cultured in medium containing 0 or 0.5 µM resveratrol for 1 or 5 days. Resveratrol treatment for both 1 day and 5 days increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
(41 reference statements)
1
21
0
Order By: Relevance
“…High concentration (2.0 μM) significantly reduced the total blastocyst formation rate compared to the control or low concentrations (Table 1). This was consistent with previous studies indicating that high concentrations of resveratrol might have negative effects on embryonic development [25,26]. However, since different results have been reported, differences in the fertilization method, the culture medium used, and the mice species might be associated with such discrepancies [10].…”
Section: Discussionsupporting
confidence: 92%
“…High concentration (2.0 μM) significantly reduced the total blastocyst formation rate compared to the control or low concentrations (Table 1). This was consistent with previous studies indicating that high concentrations of resveratrol might have negative effects on embryonic development [25,26]. However, since different results have been reported, differences in the fertilization method, the culture medium used, and the mice species might be associated with such discrepancies [10].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the supplementation of the embryo culture medium with resveratrol enhanced the developmental rate till the blastocyst stage. Previous reports have highlighted the beneficial effects of resveratrol on the embryonic development of porcine and bovine embryos had been reported previously [ 22 , 37 ]. In the present study, the incubation of 8-cell stage bovine embryos in the resveratrol-containing medium resulted in an increase in the expression level of SIRT1 in the resultant blastocysts [ 22 ].…”
Section: Discussionmentioning
confidence: 93%
“…Previous reports have highlighted the beneficial effects of resveratrol on the embryonic development of porcine and bovine embryos had been reported previously [ 22 , 37 ]. In the present study, the incubation of 8-cell stage bovine embryos in the resveratrol-containing medium resulted in an increase in the expression level of SIRT1 in the resultant blastocysts [ 22 ]. Furthermore, resveratrol had no effect on the mitochondrial number and total cell number of blastocysts.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Consistent with these reports, we found that post-warming blastocysts had lower ATP content than their fresh counterparts. Furthermore, the ATP content in frozen-thawed embryos were still low after 24 hr of incubation (1.31 pM, Figure 5-A) compared with fresh blastocysts examined under the same conditions (1.77 pM, Abe et al, 2017), in addition mitochondrial copy number in the frozen-thawed embryos were also low compared with those in fresh embryos (Figure 3).…”
Section: Discussionmentioning
confidence: 92%